2012
DOI: 10.1007/s11033-012-1963-7
|View full text |Cite
|
Sign up to set email alerts
|

G241R and K469E polymorphisms of intercellular adhesion molecule 1 (ICAM-1) could predispose to Hashimoto thyroiditis

Abstract: This study examined firstly the possible association of G241R and K469E single nucleotide polymorphisms (SNPs) of ICAM-1 gene with the occurrence of Hashimoto thyroiditis (HT). G241R and K469E SNPs in DNA from peripheral blood leukocytes of 190 HT and 247 healthy controls were investigated by real-time PCR combined with melting curve analysis using fluorescence-labeled hybridization probes. There was a significant increase of ICAM-1 241R allele frequency in patients with HT compared with healthy controls (P = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Emerging evidence suggests that single-nucleotide polymorphisms (SNPs) in immunoregulatory genes may functionally impede the normal development of central and peripheral tolerance and alter the interaction of T cells with antigen-presenting cells (APCs) in the immune synapse. Numerous studies have found that gene polymorphisms, such as CTLA4 ( 93 95 ), TNF -308 ( 96 ), TRAF1 ( 97 ), microRNA ( 98 ), NFKB1 ( 99 ), NLRP1 ( 100 ), ICAM-1 ( 101 ), ZFAT ( 102 ) and so on, are significantly associated with AITD. Racial variations in AITD prevalence further accentuate potential genetic polymorphisms and the role of genetic susceptibility in the etiology of AIT ( 103 ).…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence suggests that single-nucleotide polymorphisms (SNPs) in immunoregulatory genes may functionally impede the normal development of central and peripheral tolerance and alter the interaction of T cells with antigen-presenting cells (APCs) in the immune synapse. Numerous studies have found that gene polymorphisms, such as CTLA4 ( 93 95 ), TNF -308 ( 96 ), TRAF1 ( 97 ), microRNA ( 98 ), NFKB1 ( 99 ), NLRP1 ( 100 ), ICAM-1 ( 101 ), ZFAT ( 102 ) and so on, are significantly associated with AITD. Racial variations in AITD prevalence further accentuate potential genetic polymorphisms and the role of genetic susceptibility in the etiology of AIT ( 103 ).…”
Section: Discussionmentioning
confidence: 99%